Emergence of the probabilistic language in the Primary Education classroom - Vasquez, Claudia (2018)
This paper presents an analysis of how students of a second basic year approach the probability of occurrence of an event through the use of terms and expressions that constitute a qualitative scale of the degrees of possibility of occurrence of an event. For this, this study focuses on probabilistic language, used by students, understood as a precise and specialized language that allows the qualitative expression of the probability of occurrence of a certain event, which in turn constitutes a support for the development of probabilistic literacy. With this purpose, a set of probabilistic tasks was implemented through which it is intended to access the probabilistic language used by the students of the first years of Primary Education when faced with situations of uncertainty. This allowed us to analyze and describe how the first linguistic elements associated with probability emerge during a process of instruction with students of Primary Education. The results show a strong predominance of terms and verbal expressions coming from the common language linked mainly to the intuitive meaning of probability, which move towards probabilistic concepts. It ends with the proposal of a set of phases to promote the acquisition and development of probabilistic literacy in Primary Education.